THE MODERN CONCEPT OF THE PATHOGENESIS OF INFECTIOUS DISEASE - V. F. Uchaykin (LLC "Diagnostics and Vaccines", 2015)
The concept of the pathogenesis of infectious disease is based on the teaching about the mode of entry of infection, the tropic organ and variability. The course of disease, immediate and long term consequences depend on the mode of entry. An infection that comes via oropharynx, airway, gastrointestinal tract or via skin leads to development of a proper portal of entry and the immune system provides adequate immune response. That results in typical symptoms, cyclical clinic progression and usually leads to the recovery with the formation of full sterile immunity. In case of parenteral route of infection, which includes perinatal way, there is no proper portal of entry and the disease can eventually become fulminant or take chronic course involving visceral organs. It can happen because of changes in the mechanism of tropism and emergence of new target visceral organs. For the complete recovery the pathogen or its mediators should be present in the primary focus of infection. It is suggested, that HIV, HCV, hepatitis B virus, tetanus, rabies and other infectious diseases with involvement of visceral organs, as well as all slow infections, should be treated as infectious diseases with the parental way of infection, progressing with changes in tropism. This leads to the emergence of new tropic substrates in visceral organs. The teaching about the portal of entry of infection, tropism, emergence of new target visceral organs must form the basis of contemporary infectology.